Microdosimetry at the CATANA 62 MeV proton beam with a sealed miniaturized TEPC. (August 2019) - Conte, V.; Bianchi, A.; Selva, A.; Petringa, G.; Cirrone, G.A.P.; Parisi, A.; Vanhavere, F.; Colautti, P.
Highlights: Miniature Tissue Equivalent Proportional Counters can work without gas-flow. The new sealed mini-TEPC gives reproducible results over a period of 4 months. The new mini-TEPC can be used as a precise LET-monitor in proton therapy. The new mini-TEPC measurements result in a reasonable RBE-assessment. The mini-TEPC can be used for a comparative study of different radiotherapy centres. Abstract: A new mini-TEPC with cylindrical sensitive volume of 0.9 mm in diameter and height, and with external diameter of 2.7 mm, has been developed to work without gas flow. With such a mini counter we have measured the physical quality of the 62 MeV therapeutic proton beam of CATANA (Catania, Italy). Measurements were performed at six precise positions along the Spread-Out Bragg Peak (SOBP): 1.4, 19.4, 24.6, 29.0, 29.7 and 30.8 mm, corresponding to positions of clinical relevance (entrance, proximal, central, and distal-edge of the SOBP) or of high lineal energy transfer (LET) increment (distal-dose drop off). Without refilling the microdosimeter with new gas, the measurements were repeated at the same positions 4 months later, in order to study the stability of the response in sealed-mode operation. From the microdosimetric spectra the frequency-mean lineal energy y - F and the dose-mean lineal energy y - D were derived and compared with average LET values calculated by means of Geant4 simulations. The comparison points out, in particular, a good agreement between microdosimetric y - D and the total dose-average L E T ¯ d, which is the average LET of the mixed radiation field, including the contribution by nuclear reactions.